2018
DOI: 10.1007/s10238-018-0520-7
|View full text |Cite|
|
Sign up to set email alerts
|

Mixed-phenotype acute leukemia characteristics: first report from Iran

Abstract: Mixed-phenotype acute leukemia (MPAL) is the infrequent type of acute leukemia characterized by immunophenotypic and/or cytochemical features of both lineages, but the diagnosis of this disease still is a challenge. In this study, we analyzed immunophenotyping, cytochemistry and frequency of MPAL patients to better diagnosis of MPAL characteristics according to WHO 2016 criteria for the first time in Iran. In this retrospective study, 27 patients were diagnosed as MPAL based on WHO 2016 criteria during 2014-20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
1
4
0
1
Order By: Relevance
“…However, literature data on prevalence of MPAL between gender distribution are not clear, as Deffis‐Court et al 22 and Matutes et al 10 showed that MPAL cases were more frequent in males (63%) and females (68%), respectively. In our data and similarly to other studies, there was no significant difference in patients’ and clinical disease characteristics between MPAL subsets 20 . However, we found that despite comparable rate of CR in T/myeloid and B/myeloid leukemia, the pEFS was significantly better within patients with T/myeloid phenotype ( P = .047).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, literature data on prevalence of MPAL between gender distribution are not clear, as Deffis‐Court et al 22 and Matutes et al 10 showed that MPAL cases were more frequent in males (63%) and females (68%), respectively. In our data and similarly to other studies, there was no significant difference in patients’ and clinical disease characteristics between MPAL subsets 20 . However, we found that despite comparable rate of CR in T/myeloid and B/myeloid leukemia, the pEFS was significantly better within patients with T/myeloid phenotype ( P = .047).…”
Section: Discussionsupporting
confidence: 89%
“…The incidence of BCR/ABL1 -positive disease is reported to be higher in adults (15%-30%) than in pediatric patients (4%-16%), especially in B/myeloid phenotype, while MLL rearrangements are reported more often in children (11%-12%) compared to adults (4%-8%). 5,11,[18][19][20] As there is a large number of publications indicating the benefits of TKIs in the treatment of MPAL patients with BCR/ABL1 fusion, 11,20,21 evaluation of BCR/ABL1 is a standard way for better diagnosis in patients with MPAL, especially that this is a population with higher rates of this fusion than other childhood AL. 20 In our study, MPAL patients included 66.7% males and 33.3%…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer is an uncontrolled growth of the body’s cells, the most common form of which is in children as hematologic malignancies, accounting for 44% of the cancers diagnosed in children (33% leukemia and 11% lymphoma) (1). Acute Lymphoblastic Leukemia (ALL) accounts for about 75% of leukemia cases, and is considered as a clonal malignancy of bone marrow in which early lymphoid precursors proliferates, leading to replacement of them with normal hematopoietic cells in the bone marrow (2).…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, a avaliação de rearranjos de BCR, ABL1 e MLL também fazem parte da investigação desse tipo de leucemia. (Poopak, B. et al, 2018) Segundo Teke et al (2017) a LMA, a expressão do antígeno TdT demonstra um mau prognóstico que tem efeito na sobrevida do paciente. Os antígenos na superfície dos blastos não afetam o prognóstico de LMA isoladamente.…”
Section: Discussõesunclassified